Propuesta para la implementación de un sistema de gestión de calidad bajo la norma ISO 9001:2015 en una empresa comercializadora (2016)
Internal audit is an objective, independent, and documented evaluation process that allows organizations to add value and provide improvements to each of their operations. This process allows to identify commercial intentions, errors in processes and procedures, evaluate risks and opportunities, create preventive and corrective actions, verify the implementation of the changes and satisfy the requirements of the interested parties. The objective of this paper is to design an instrument for the audit process of quality management systems based on the requirements of ISO 9001: 2015.